Sustainable poverty reduction through social assistance: Modality, context, and complementary programming in Bangladesh - Ahmed, Akhter; Hidrobo, Melissa; Hoddinott, John F.; Kolt, Bastien; Roy, Shalini; Tauseef, Salauddin (American Economic Association, 2025)
Social assistance programs can increase consumption and reduce poverty, but less is known about whether these impacts are sustained after programs end or how design and context influence sustainability. Using data collected in two regions of Bangladesh four years after a randomized intervention ended, we find that combining cash transfers with complementary programming led to sustained increases in consumption and reductions in poverty. Combining food transfers with complementary programming showed similar patterns to a lesser extent. Cash alone had context-specific sustained effects; food alone had no sustained impacts. Results suggest that context, modality, and complementary programming matter for sustained impacts. (JEL D12, E21, I32, I38, O15)